10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih (University of Maribor Press, 2024)
10th National Conference on Local Safety and Security: Local Safety and Security – Peaceful, Safe and Inclusive Society and Security in Local Communities. Conference proceedings comprise peer-reviewed papers presented at the 10th National Conference on Safety and Security in Local Communities, which took place in Kočevje in November 2024. Safety and security in local communities remain the main topic of the conference, with a special focus of this year’s conference on a peaceful safe and inclusive society. Papers present the result of the research programme Safety and Security in Local Communities – Comparison of Rural and Urban Environments of the Faculty of Criminal Justice and Security, University of Maribor and collaboration with practitioners from the police and local communities. Papers focus on various aspects of ensuring safety and security and the perception of threats in local communities, problem-solving in multicultural communities, crime characteristics and preventative measures, prevention of juvenile delinquency, attitudes towards punishment, cyber security, and sustainable development. In addition, papers present examples of good practices.